Enhanced Solubility of Rapeseed Meal Protein Isolates Prepared by Sequential Isoelectric Precipitation - Hristo Kalaydzhiev; Radoslav Georgiev; Petya Ivanova; Magdalena Stoyanova; Cristina L. M. Silva; Vesela I. Chalova (Foods, 2020)
The solubility of plant protein isolates is a key determinant of their potential application. Two protein isolates (PI) from ethanol-treated industrial rapeseed meal, PI10.5–2.5 and PI2.5–8.5, were prepared by sequential isoelectric precipitation of alkali-extracted proteins (pH 12) starting from pH 10.5 to 2.5 or from pH 2.5 to 8.5, respectively. Biochemical analyses revealed that PI2.5–8.5 contained a higher amount of crude protein (72.84%) than PI10.5–2.5 (68.67%). In the same protein isolate, the level of total phenols (0.71%) was almost two-fold higher than that in PI10.5–2.5 (0.42%). No glucosinolates were established in both protein isolates. SDS-PAGE analysis demonstrated that PI10.5–2.5 contained 10 to 15 kDa protein fractions in a relatively higher amount, while PI2.5–8.5 was enriched in 18 to 29 kDa protein fractions. PI10.5–2.5 exhibited high solubility, varying from 41.74% at pH 4.5 to 65.13% at pH 6.5, while PI2.5–8.5 was almost two-fold less soluble under the same conditions. Up to pH 5.5, the addition of NaCl at 0.03 and 0.25 M diminished the solubility of PI2.5–8.5, while the solubility of PI10.5–2.5 was increased. The supplementation of PI10.5–2.5 with 0.25 M NaCl enhanced the protein solubility to 56.11% at pH 4.5 and 94.26% at pH 6.5. The addition of 0.03 M NaCl also increased the solubility of this protein isolate but to a lower extent. Overall, the approach for sequential precipitation of proteins influenced the biochemical characteristics, protein fractional profile and solubility of prepared protein isolates.